Madrasah Diniyah Learning Patterns: Curriculum Design Studies and Pedagogical Practices - Miranu Triantoro; Udin Erawanto; Hesty Puspita Sari (Al-Hayat: Journal of Islamic Education, 2023)
This research aims to describe the learning patterns of Islamic madrasas. Focusing on curriculum design and practice on the pedagogical abilities of students. Santri here refers to the research location, which is located at the Nurul Ulum Blitar Islamic boarding school. This research is a type of qualitative research with a descriptive approach. Data was collected through interviews, observation, and documentation techniques and processed through descriptive analysis. The analysis consists of three activity streams carried out simultaneously: data collection, data reduction, and conclusion or data verification. The study results show that the learning pattern at Madrasah Diniyah Nurul Ulum uses a mixed system. The system seeks to combine traditional and modern methods. The learning pattern of Madrasah Diniyah Nurul Ulum integrates the curriculum, aspects of pedagogy and professionalism, and the degree of educator education. The learning curriculum at Madrasah Diniyah Nurul Ulum combines conservative salafiyah classes and modern kalafiyah. The pedagogical ability of students can be found in learning in the form of studying various kinds of books, which are divided into Ula and Wustho levels. Professionalism here is a solid learning pattern for students, morning, afternoon, evening and night, to hone discipline and expertise. The degree of educator education is the profile of the Nurul Ulum Islamic boarding school teacher with a reasonable level. Integrating the four aspects above, this Madrasah presents the Nurul Ulum learning pattern as its advantage.